Wordy expressions of integrity and reform in the use of holy Quran (Journal of the College of Education for Women, 2019)
The aim of this message to monitor this phenomenon throught the Quran , which is the constitution of the Islamic nation and Hariatha as well as to express kasalah integrity , justice honesty , patience , abd pacr .We feel this vocabulary to hight athical values advocated by the Quran and the need to build commitment to the orthodox society free of corruption that leads ta a disorder of the human society .The outcome of the study the researcher found that faith to a number of results was most notably the advent of righteusness in the Holy Quran meaning of comprehensive RPR spacious field and breadth Maadenh .